ANALISIS PERENCANAAN STRUKTUR GEDUNG BETON BERTULANG TAHAN GEMPA DENGAN METODE SISTEM RANGKA PEMIKUL MOMEN KHUSUS PADA BANGUNAN TIGA ( 3 ) LANTAI KAMPUS SEKOLAH TINGGI FILSAFAT KATOLIK ( STFK ) LEDALERO KABUPATEN SIKKA - Fransiskus Bala Werang (Program Studi Teknik Sipil, 2021)
The Catholic School of Philosophy (STFK) Ledalero is a Catholic higher education institution located in Maumere, Sikka Regency, East Nusa Tenggara Province, Indonesia. STFK Ledalero is undertaking the construction of a new lecture building located in the Candraaditya complex, Wairklau Street, Madawat Subdistrict, Alok District. This area is categorized as a high seismic zone (zone 5 on the Indonesian earthquake map), thus requiring careful structural design to ensure earthquake resistance. This study begins with literature review, determination of design criteria, preliminary design planning, structural modeling, structural loading, and structural analysis using the Special Moment Resisting Frame System (SRMPK) method with SAP2000 software version 14. The results show that the structure is capable of withstanding the applied loads, including seismic forces. The reinforcement details are as follows: the main beams in both X and Y directions have dimensions of 400 × 700 mm, with top support reinforcement of 10D19, bottom support 8D19, top span 10D19, bottom span 8D19, and stirrups Ø10-100 at supports and Ø10-150 in spans. The secondary beams are 300 × 600 mm, with 8D19 and 6D19 reinforcements for the top and bottom at both support and span, and stirrups Ø10-100 at supports and Ø10-150 in spans. Columns have dimensions of 600 × 600 mm with 10D19 longitudinal reinforcement and two-legged stirrups Ø10-100. The floor slabs are reinforced with Ø10-200 in both X and Y directions for spans, and Ø10-166 in X and Y directions at supports.